Penentuan Sekolah Terdekat Untuk Visitasi Asesor Menggunakan Metode Algoritma K-Means Berbasis Web - Zainal Ikhwan, Muhammad; Putra Eka Prismana, IGL; Mashuri, Chamdan (Inovate, 2021)
The closest school determination to visitation of assessors is a step made to facilitate the assessors to implement school accreditation. School Accreditation is an effort to improve the quality of National Education. The provincial school accreditation body or Madrasah (BAP-S/M) conducts recruitment of assessors and is divided by a number of places or regions to perform visitation. The Research aims to design a nearby school-based website determination System and implement the K-means method for such systems. This method is used to group the data by specifying the number of clusters or previous groups, calculating the centroid Center and grouping the data that has the similarity of variables. This method calculation generates multiple iterations that have cluster values. Of these iterations used the least number of cluster values to determine the group of schools within one province. The result of this research is a nearby school determination information system for the visitation of assessors. The testing of this system was conducted at the school in the province of East Java with the coordinate point as a variable of latitude and longitude coordinates. From the test results with 20 school data data into 3 clusters, obtained the result of cluster 1 with the coordinate center point (-7,213605, 112,769658) amounting to 8 schools, cluster 2 with the coordinate center point (-7,202459, 112,636323) amounting to 7 school and cluster 3 with coordinate center point (-7,249299, 112,636909) amounting to 5 schools. Keywords : K-Means, Clustering, Accreditation, School, Web.